2012
DOI: 10.1016/j.dental.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of third-body media particles and their effect on in vitro composite wear

Abstract: Objectives The purpose of this study was to compare four medium particles currently used for in vitro composite wear testing (glass and PMMA beads and millet and poppy seeds). Methods Particles were prepared as described in previous wear studies. Hardness of medium particles was measured with a nano-indentor, particle size was measured with a particle size analyzer, and the particle form was determined with light microscopy and image analysis software. Composite wear was measured using each type of medium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
11
1
1
Order By: Relevance
“…It is important to determine the mechanical and esthetic behavior of the materials placed within this structure over time. Many in vivo and in vitro test methods have been developed in the literature to carry out mechanical and esthetic resistance behavior of biomaterials [3,5,12,13]. However, researchers have a tendency to study in vitro because of in vivo studies have taken a very long time, the costs are high, and for ethical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine the mechanical and esthetic behavior of the materials placed within this structure over time. Many in vivo and in vitro test methods have been developed in the literature to carry out mechanical and esthetic resistance behavior of biomaterials [3,5,12,13]. However, researchers have a tendency to study in vitro because of in vivo studies have taken a very long time, the costs are high, and for ethical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence was repeated at a rate of 120 contacts/ min. Lawson et al demonstrated how the PMMA slurry seems to function as a practical medium for use in the three-body wear test when the Alabama type wear simulators are used 15) . Therefore, we used PMMA beads as a third-body medium.…”
Section: Discussionmentioning
confidence: 99%
“…Shape is important in two-body abrasion [46] , with angular protuberances producing more wear than rounded ones, even if the rounded ones are harder. This factor is less important in three-body abrasion, as the loose particles reorient themselves during contact which reduces antagonistic interactions [47] .…”
Section: Mechanisms Of Wearmentioning
confidence: 99%